Targeting connexin 43 expression via scaffold mediated delivery of antisense oligodeoxynucleotide preserves neurons, enhances axonal extension, reduces astrocyte and microglial activation after spinal cord injury - Chin, Jiah Shin (2023)
Injury to the central nervous system (CNS) provokes an inflammatory reaction and secondary damage that result in further tissue damage and destruction of neurons away from the injury site. Upon injury, expression of connexin 43 (Cx43), a gap junction protein, upregulates and is responsible for the spread and amplification of cell death signals through these gap junctions. In this study, we hypothesise that the downregulation of Cx43 by scaffold-mediated controlled delivery of antisense oligodeoxynucleotide (asODN), would minimise secondary injuries and cell death, and thereby support tissue regeneration after nerve injuries. Specifically, using spinal cord injury (SCI) as a proof-of-principle, we utilised a fibre-hydrogel scaffold for sustained delivery of Cx43asODN, while providing synergistic topographical cues to guide axonal ingrowth. Correspondingly, scaffolds loaded with Cx43asODN, in the presence of NT-3, suppressed Cx43 up-regulation after complete transection SCI in rats. These scaffolds facilitated the sustained release of Cx43asODN for up to 25 days. Importantly, asODN treatment preserved neurons around the injury site, promoted axonal extension, decreased glial scarring, and reduced microglial activation after SCI. Our results suggest that implantation of such scaffold-mediated asODN delivery platform could serve as an effective alternative SCI therapeutic approach.